Eletromiografia e teste de força máxima para avaliação de protocolo de acupuntura para dor de joelho de corredores - Siqueira, Ana Paula Rehme (2015)
Pain in the lower members is very common in athletes and may represent a limiting aspect to income. According to epidemiological studies, between 27% and 70% of the runners have some type of injury during the period of one year, which causes discomfort during practice and generates poor performance in competitions. In the pursuit of mitigation and / or solution to the pain of running athletes, acupuncture may be beneficial, as this technique is known for its analgesic effects applied on knee area. The objective of this study was to analyze parameters related to knee pain correlating the musculature strength parameters evaluated in corridors undergoing acupuncture treatment. It conducted a descriptive study from January to June 2015 with 34 runners, aged 20-52 years, of both sexes, who presented pain in the knee region. Volunteers completed the McGill Pain Questionnaire and the Visual Analogue Scale and were subjected to the maximum force test with electromyographic evaluation of the rectus femoris, vastus lateralis and vastus and quadriceps strength evaluation. They received five weekly attendances following the acupuncture protocol developed for this study. After, they were again subjected to strength testing and completing the questionnaire and the pain scale. All volunteers reported feeling decrease knee pain after treatment, which was assessed using the McGill Pain Questionnaire initially obtained median of 17.5 and after treatment, 6.5 (62.9% improvement). And through the Visual Analogue Scale (VAS), which initially had an median of 6.0 and after the average treatment of 3.0 (an improvement of 50.0%) and p <0.001 for both. The affected limb mean strength was 20kgf and 27kgf this was increased to after treatment (34% increment and p <0.001). For the contralateral member, the initial average strength was 22kgf and after treatment was 28kgf (increase of 25% and p <0.001). To prove the strength gain through the amplitude of the electromyographic signal, there was an increase in the number of motor unit recruitment for the three muscles evaluated in both members. The affected member of the rectus femoris muscle had increased by 43% (p <0.001), vastusvmuscle of 25% (p <0.001) and vastus lateralis of 16% (p = 0.025). For the contralateral leg, the rectus femoris muscle was increased by 17% (p = 0.023), the vastus medialis of 32% (p = 0.029) and lateral vastus 27% (p = 0.002). The median frequency no difference in conduction velocity of action potentials in both members. It is concluded that the proposed protocol is effective in reducing painful symptoms in knees region runners athletes, interfering with the gain in strength and muscle balance.